The Role of Controlled Substance Use in Diversion Outcomes Among Mentally Ill Offenders: A Pilot Study - Boland, Jennifer K. (International journal of offender therapy and comparative criminology, 2018)
Diversion programs offer opportunities to offenders with substance abuse or mental illness to attend treatment as an alternative to incarceration. The present study identified variables associated with drug relapse and recidivism and the moderating role of substance use on recidivism in a diversion sample. Data were collected from 80 clients with psychotic disorders from a diversion program in New York City. Outcomes were examined after 6 and 12 months of program participation. Individuals who used controlled substances other than alcohol or cannabis were more likely to have a positive toxicology result than those who used alcohol or cannabis only or those with no alcohol/drug history. Individuals with schizoaffective disorder were more likely to be rearrested than individuals with other diagnoses, as were those with a violent offense (e.g., assault, robbery). Positive toxicology results were unrelated to rearrest and did not moderate recidivism, suggesting substance abuse may be only indirectly related to rearrest among diverted offenders.